(7x+1)+(13x+9)=90

Simple and best practice solution for (7x+1)+(13x+9)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+1)+(13x+9)=90 equation:


Simplifying
(7x + 1) + (13x + 9) = 90

Reorder the terms:
(1 + 7x) + (13x + 9) = 90

Remove parenthesis around (1 + 7x)
1 + 7x + (13x + 9) = 90

Reorder the terms:
1 + 7x + (9 + 13x) = 90

Remove parenthesis around (9 + 13x)
1 + 7x + 9 + 13x = 90

Reorder the terms:
1 + 9 + 7x + 13x = 90

Combine like terms: 1 + 9 = 10
10 + 7x + 13x = 90

Combine like terms: 7x + 13x = 20x
10 + 20x = 90

Solving
10 + 20x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 20x = 90 + -10

Combine like terms: 10 + -10 = 0
0 + 20x = 90 + -10
20x = 90 + -10

Combine like terms: 90 + -10 = 80
20x = 80

Divide each side by '20'.
x = 4

Simplifying
x = 4

See similar equations:

| 2(4-3x)-10=2x-74 | | 4x^3-9x^2-2=0 | | 13y-1.8=-5y+3.6 | | 4(5c+1)-26=17c+2 | | 33t=-46 | | X*.6=25 | | 5√6/4√50 | | 3x-8=4(x+4) | | 3m-7+m+23= | | 3x+29=6x+8 | | 4(x-3)=x-12 | | 8x%3-2x%4=-14 | | 4x-27andX+39= | | -11n-7=11 | | k/6-7=-4 | | 2(2x+5)+2x=250 | | 6x-15=5x+6-2x | | 1/2in(e^6) | | (5√6)/(4√50) | | (12n+99)+(8n+8)= | | 20n-16=0 | | 35x^3+63x^5+21x^6= | | a/a+4=3-4/a+4 | | r/6=-9+3 | | 2(3x+2)=2(x-4) | | 7x+70=x+50 | | f(x)=3x^4-8x^3+5 | | X-(13)=21 | | 7(2x-7)-5=14x-54 | | x+50=4x+20 | | x+50=3x+50 | | x2/2=8 |

Equations solver categories